New ring of a class of Bessel integral operators. Issue 8 (2nd August 2016) - Assal, Miloud; Zeyada, Nasr A.
ABSTRACT: In this paper, we introduce a new ring of ponderation functions which allowed us to describe and classify a large class of ring of Bessel integral operators. The main result is to give an explicit form of some ideals of such a ring of operators.